Flashcards as A Means to Improve EFL Learners’ Vocabulary Mastery - Wahyuni, Sri; Yulaida, Handayani (JEELS (Journal of English Education and Linguistics Studies), 2014)
The objective of this study is to know whether the use of flashcards can improve the vocabulary mastery of Junior High School Students in Indonesian. The research design used in this study is Classroom Action Research (CAR) in which it was conducted in two cycles. Each cycle consisted of planning, implementing, observing, and reflecting. The research instruments used are observation checklist, test, field note, and documentation. In the implementation of improving students’ vocabulary mastery by using flashcards the researchers stimulated students’ prior knowledge by asking question, introduction the topic, and introduction about the media.The implementation of the planning in the first cycle was not successful. In the second cycle, the result of the students’ evaluation test showed that 84% of the student passed the minimum score in the criteria of success, and 80% of the students did the activities designed in the second cycle. From the result, it can be concluded that the implementation of flashcards is successful in improving the students’ vocabulary mastery.